Management of exercise-induced bronchospasm in NCAA athletic programs - Parsons, J. P.; Pestritto, V.; Phillips, G.; Kaeding, C.; Best, T. M.; Wadley, G.; Mastronarde, J. G. (Medicine & Science in Sports & Exercise, 2009)
Purpose: The prevalence of exercise-induced bronchospasm (EIB) is significantly higher in athletes than that in the general population and can result in significant morbidity in young, competitive athletes. Guidelines emphasize that education and written treatment protocols improve clinical outcomes for asthmatics. Evidence also supports objective testing when EIB is suspected, when there is immediate availability of rescue inhalers, and when there is involvement of asthma specialists in the care of asthmatic athletes. We sought to determine how EIB is managed at the National Collegiate Athletic Association (NCAA) sports medicine programs.